2022
DOI: 10.58968/tj.v1i1.95
|View full text |Cite
|
Sign up to set email alerts
|

Development of Islamic Microfinance

Abstract: This study tries to review research on sustainable microfinance development in Scopus indexed journals. This analysis uses descriptive statistical analysis based on 319 selected papers related to microfinance sustainable development from both national and international journals. All samples of published journals have been published for 27 years from 1996 to 2022. The data is then processed and analyzed using the VOSviewer application program to find out the bibliometric visualization map for sustainable develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The sampling technique used in this research is purposive non-probability sampling method, which aims to fulfill certain information in accordance with the desired research objectives. The application of research with bibliometrics on the topic of Islamic economics and finance has been carried out by several researchers such as Kholiq et al, (2022), Sari (2022aSari ( , 2022b, Izza (2021Izza ( , 2022, Putri (2022), As-Salafiyah (2022), Ikhwan (2021), Riani (2021), As-Salafiyah & Rusydiana (2022) and Khairunnisa & Uula (2022).…”
Section: Methodsmentioning
confidence: 99%
“…The sampling technique used in this research is purposive non-probability sampling method, which aims to fulfill certain information in accordance with the desired research objectives. The application of research with bibliometrics on the topic of Islamic economics and finance has been carried out by several researchers such as Kholiq et al, (2022), Sari (2022aSari ( , 2022b, Izza (2021Izza ( , 2022, Putri (2022), As-Salafiyah (2022), Ikhwan (2021), Riani (2021), As-Salafiyah & Rusydiana (2022) and Khairunnisa & Uula (2022).…”
Section: Methodsmentioning
confidence: 99%
“…Several similar studies on the topic of Islamic economics and finance, for example, are studies conducted by Niswah (2020), Ruhana (2021), Riani & Fatoni (2022), Izza et al, (2021), Putri (2022), Uula & Maziyyah ( 2022) and Sari (2022). Based on the results of the initial search analysis in conducting an analysis of the metadata collected and obtained after running the search query, information and general descriptions regarding research articles with the keyword "takaful efficiency" are obtained.…”
Section: Methodsmentioning
confidence: 99%
“…VOSviewer runs on a large number of hardware and operating system platforms and can be started directly from the internet. Other research using bibliometric on Islamic economics and finance can be found in As-Salafiyah (2022), Izza (2022), Riani (2021), Sari (2022), Ikhwan (2021), Ruhana (2021), As-Salafiyah & Kartikawati (2022), Taqi et al, (2021), andPutri (2022).…”
Section: Methodsmentioning
confidence: 99%